Peripubertal proliferation of progenitor cells in the preoptic area of Japanese quail (Coturnix japonica) - Mouriec, Karen (2013)
Brain structures related to reproduction are thought to depend on the action of gonadal steroids acting either during early life (organizing irreversible effects) or adulthood (activating transient effects). More recently puberty has become a focus of attention and it was demonstrated that action of sex steroid hormones at this time plays a critical role in the final organization of brain and behavior. We studied by BrdU immunohistochemistry the ontogeny from hatching to sexual maturity of a previously identified cell population in the preoptic area labeled by a BrdU injection at the end of embryonic period (E12) of sexual differentiation in male and female Japanese quail. After an initial increase between E12 and hatching, the density of BrdU-immunoreactive cells decreased until the beginning of puberty but then increased again during sexual maturation in the caudal preoptic area specifically. Divisions of these cells took place in the brain parenchyma as indicated by the large numbers of pairs of labeled cells. No sex difference affecting these processes could be detected at any stage of development. Large numbers of new cells thus arise around puberty in the caudal preoptic area and presumably contribute to the reorganization of this structure that precedes the emergence of adult reproductive behaviors.